Efficacy of a new attenuated duck parvovirosis vaccine in Muscovy ducks. (20th September 2014) - Maurin‐Bernaud, L.; Goutebroze, S.; Merdy, O.; Chanay, A.; Cozette, V.; Gros, F‐X Le
Abstract : The efficacy of a new live attenuated parvovirosis vaccine was tested in conventional ducklings against Derzsy's disease by comparing two vaccination regimens. Ducklings were vaccinated with either one injection at 17 days of age or two injections at 1 and 17 days of age. Controls and vaccinated ducklings were challenged with a virulent Derzsy strain at 21 days of age (day 20). Weight was measured on days 20, 34 and 42/43. Surviving birds were necropsied on day 42/43. Protection rates were significantly higher in the groups vaccinated once (90 per cent, P=0.003) and twice (95 per cent, P<0.001) than in the control group (59 per cent). The bodyweight was significantly higher in both vaccinated groups than in the control group on day 34 (P=0.008 and P<0.001, respectively) and day 42/43 (P<0.001 for both groups). The growth was significantly higher in the group vaccinated twice than the group vaccinated once on day 34 (P=0.047) and day 42/43 (P=0.017). Both vaccination regimens provided a quick onset of immunity. The higher weight gain in the group vaccinated twice suggests that an early vaccination at hatchery followed by a second injection at 17 days of age is an optimal and practical schedule to prevent parvovirosis.